EFFECT OF HARVEST TIME ON GROWTH PERFORMANCE, BIOMASS AND PRODUCTIVITY OF Kappaphycus alavarezii IN WAWORADA BAY - Hamdu, Hamdu; Junaidi, Muhammad; Dwi Hari Setyono, Bagus (Jurnal Media Akuakultur Indonesia, 2022)
West Nusa Tenggara has a lot of marine and fishery potential, one of which is Waworada Bay, the development of Seaweed is increasing, and it is the latest breakthrough and helps the economy of coastal communities in West Nusa Tenggara. The purpose of this study was to determine the effect of planting depth on the growth of Eucheuma cottonii seaweed and to determine the growth potential with different depths on the growth of Eucheuma cottonii seaweed. The depths used in this study were a depth of 20 cm, 30 cm, 40 cm, 50, cm and 60 cm with the long line method and further tested for carrageenan content at the Base Laboratory of the Aquaculture Study Program, University of Mataram. This study used a completely randomized design (CRD) consisting of 5 treatments and 3 replications to obtain 15 experimental units. P1: Depth 20 cm, P2: Depth 30 cm, P3: Depth 40 cm, P4: Depth 50 cm, P5: Depth 60 cm. The results showed that different planting distances between 20 cm, 30 cm, 40 cm had no significant effect on the growth of Eucheuma cottonii seaweed, while at a depth of 50 cm and 60 cm it had an effect so that seaweed growth was inhibited and at a depth of 20 cm, 30 cm and 40 cm. cm has the potential for faster growth, in contrast to the depth of 50 cm and 60 cm the type of seaweed Eucheuma cottonii has a slower growth so that it shows a significant effect at each depth.